2023
DOI: 10.3390/educsci13090856
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities of Generative AI for Higher Education as Explained by ChatGPT

Rosario Michel-Villarreal,
Eliseo Vilalta-Perdomo,
David Ernesto Salinas-Navarro
et al.

Abstract: ChatGPT is revolutionizing the field of higher education by leveraging deep learning models to generate human-like content. However, its integration into academic settings raises concerns regarding academic integrity, plagiarism detection, and the potential impact on critical thinking skills. This article presents a study that adopts a thing ethnography approach to understand ChatGPT’s perspective on the challenges and opportunities it represents for higher education. The research explores the potential benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(52 citation statements)
references
References 41 publications
1
49
0
2
Order By: Relevance
“…The revolutionary influence of artificial intelligence (AI) is gaining a profound recognition, particularly in the scope of higher education (Grassini, 2023;Kamalov et al, 2023). The advent of AI conversational models (e.g., ChatGPT, Bard, and Bing Chat) offers an opportunity to fundamentally transform the entire educational landscape including various aspects such as teaching methods, curriculum development, educational policies, and practices (Michel-Villarreal et al, 2023;Sallam, 2023;Southworth et al, 2023). On the other hand, AI is dynamic field, characterized by rapid expansion and evolution (Dwivedi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The revolutionary influence of artificial intelligence (AI) is gaining a profound recognition, particularly in the scope of higher education (Grassini, 2023;Kamalov et al, 2023). The advent of AI conversational models (e.g., ChatGPT, Bard, and Bing Chat) offers an opportunity to fundamentally transform the entire educational landscape including various aspects such as teaching methods, curriculum development, educational policies, and practices (Michel-Villarreal et al, 2023;Sallam, 2023;Southworth et al, 2023). On the other hand, AI is dynamic field, characterized by rapid expansion and evolution (Dwivedi et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…One particular aspect where AI-based tools can be helpful is the easy access to customized educational content that matches the specific needs and preferences of students; thereby, offering personalized learning experiences (Huang et al, 2023;Kamalov et al, 2023;Sallam, 2023;Sallam et al, 2023d). Nevertheless, there are valid concerns that arose regarding the perspectives of AI-models in higher education, specifically concerns involving the inaccuracy of the information provided by these models as well as privacy concerns (Kimmerle et al, 2023;Michel-Villarreal et al, 2023;Moldt et al, 2023;Sallam, 2023). In higher education, multiple-choice questions (MCQs) are well-recognized as an objective method to evaluate the students' achievement of required competencies and intended learning outcomes despite its known limitations (Brown and Abdulnabi, 2017;Newton, 2020;Liu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This limitation of generative AI performance is particularly relevant in healthcare education, where the ability to apply knowledge creatively and critically is essential [43]. The observed limitation raises concerns about the current reliability of AI as an educational tool, which was reported in the context of various AI chatbots [7,18,34,44]. Collectively, these results highlight the critical areas for future development and improvement in AI training approaches.…”
Section: Discussionmentioning
confidence: 97%
“…There have been a number of articles, both scholarly and nonacademic, that have addressed the potential for plagiarism using ChatGPT (Keegin, 2023; Michel-Villarreal et al, 2023). This study has found that younger age groups tended to believe that Generative AI is conducive to plagiarism.…”
Section: Discussionmentioning
confidence: 99%